Probiotic supplementation prevents stress-impaired spatial learning and enhances the effects of environmental enrichment - Flynn, Cassandra M.; Blackburn, Lara M.; Yuan, Qi (Frontiers in Microbiomes, 2025)
Probiotics are live microorganisms that offer health benefits, influencing the microbiota-gut-brain axis. Probiotics can improve cognitive functions, including learning and memory, by modulating the gut microbiota, reducing inflammation, and producing neuroactive substances. This study examined the effects of probiotic supplementation prior to chronic stress or enrichment (EE) treatment on cognitive function and brain physiology. Rats received probiotics or control diet starting at 6 months of age for 3 months. They were then randomly assigned to unpredictable stress, or EE for 6 weeks, with a home cage control group on a control diet included. Results showed that probiotic supplementation prevented spatial memory impairments induced by chronic stress and enhanced learning when combined with EE. These behavioral improvements were linked to increased gut microbiome diversity. Higher levels of the microglia marker Iba-1 were found in the stressed group compared to the EE group in the locus coeruleus, which probiotic reversed. Differences in blood-brain-barrier integrity were observed between the stress and EE groups, as indicated by albumin levels. Higher levels of tyrosine hydroxylase were observed in the hippocampus of the EE groups. The interaction of probiotic supplementation, chronic stress, and environmental EE offers a promising area for enhancing cognitive function and brain health.